Probing spin-electric transitions in a molecular exchange qubit - le Mardelé, Florian; Mohelský, Ivan; Wyzula, Jan; Orlita, Milan; Turek, Philippe; Troiani, Filippo; Boudalis, Athanassios K. (Nature communications, 2025)
Electric fields represent an ideal means for controlling spins at the nanoscale and, more specifically, for manipulating protected degrees of freedom in multispin systems. Here we perform low-temperature magnetic far-IR spectroscopy on a molecular spin triangle ( Fe 3 ) and provide initial experimental evidence suggesting spin-electric transitions in polynuclear complexes. The co-presence of electric- and magnetic-dipole transitions, allows us to estimate the spin-electric coupling. Based on spin Hamiltonian simulations of the spectra, we identify the observed transitions and introduce the concept of a generalized exchange qubit. This applies to a wide class of molecular spin triangles, and includes the scalar chirality and the partial spin sum qubits as special cases. Polynuclear magnetic molecular complexes show promise as electrically controllable spin qubits. Here the authors report evidence of spin-electric transitions in the Fe3 triangle and propose it as a generalized exchange qubit, combining characteristics of spin-chirality and partial-spin sum qubits.